Aluminosilicate granules and powder

By developing aluminosilicate particles with pore sizes above 200 nm, the problem of lack of novel structures and porous structures in the prior art is solved, and the efficient adsorption and reaction promotion effect of the material is achieved.

JP7656762B1Active Publication Date: 2025-04-03JFE MINERAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024139071
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-04-03
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

There is a lack of aluminosilicate particles capable of providing novel structures in the prior art, and it is difficult to effectively prepare aluminosilicate powders with multiple pore sizes.

Method used

Through research and development, aluminosilicate particles having pore sizes above 200 nm were found, including nanotube-shaped particles and pores of various pore sizes, including coarse pores above 200 nm, mesopores between 8 nm and 200 nm, and micropores below 8 nm.

Benefits of technology

Aluminosilicate particles with novel structures are realized, and the adsorption capacity and reaction promotion capacity of the material are improved through the porous structure. It is suitable for applications such as catalysts, adsorbents and sustainable release materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656762000001_ABST
    Figure 0007656762000001_ABST
Patent Text Reader

Abstract

To provide a powder having a novel structure not found in the past. The present invention relates to an aluminosilicate granule comprising nanotube-shaped particles and having pores with a diameter of more than 200 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminosilicate granule. The present invention also relates to a powder comprising aluminosilicate granules. [Background technology]

[0002] Patent Document 1 discloses a powder containing granules formed by aggregation of halloysite containing halloysite nanotubes. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2018 / 079556 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide aluminosilicate granules having a novel structure that has not been seen before. The present invention also provides a powder. [Means for solving the problem]

[0005] As a result of extensive research into achieving the above object, the present inventors discovered granules having pores with diameters of more than 200 nm, and completed the present invention.

[0006] That is, the present invention provides the following [1] to [8]. [1] Aluminosilicate granules containing nanotube particles and having pores with a diameter of more than 200 nm. [2] The aluminosilicate granules according to [1], further having pores having a size of more than 8 nm and not more than 200 nm. [3] The aluminosilicate granule according to [2], which has, as the pores, first pores derived from the nanotube particles and second pores different from the first pores. [4] The aluminosilicate granule according to any one of [1] to [3], further having pores with a pore size of 8 nm or less. [5] The aluminosilicate granule according to any one of [1] to [4], which has first pores derived from the nanotube particles and having a pore size of more than 8 nm and not more than 200 nm, second pores different from the first pores and having a pore size of more than 8 nm and not more than 200 nm, and third pores having a pore size of 8 nm or less. [6] The aluminosilicate granules according to any one of [1] to [5], wherein the nanotube particles are nanotube aluminosilicate particles. [7] The aluminosilicate granule according to any one of [1] to [6], wherein the nanotube particles include particles derived from halloysite nanotubes. [8] A powder comprising the aluminosilicate granules according to any one of [1] to [7]. Effect of the Invention

[0007] According to the present invention, it is possible to provide aluminosilicate granules having a novel structure. The present invention also provides a powder. [Brief description of the drawings]

[0008] [Figure 1] 1 is an SEM image of granules contained in Powder 1 of the embodiment. [Diagram 2] 1 is an SEM image of granules contained in Powder 1 of the embodiment. [Diagram 3] 1 shows the pore size distribution of Powder 1 of the embodiment. [Figure 4] 1 is a graph showing the transition of viable cell count in an antibacterial test. [Diagram 5] 1 is an SEM image of granules contained in Powder 2 of the comparative example. [Figure 6] 1 is an SEM image of granules contained in Powder 2 of the comparative example. [Figure 7] 1 shows the pore size distribution of Powder 3A of the embodiment. [Figure 8]1 is an SEM image of granules contained in Powder 3 of the embodiment. [Figure 9] 1 is an SEM image of granules contained in Powder 3 of the embodiment. [Figure 10] 1 is an SEM image of granules contained in Powder 3A of the embodiment. [Figure 11] 1 is an SEM image of granules contained in Powder 3A of the embodiment. [Figure 12] 1 is an SEM image of granules contained in Powder 4A of the embodiment. [Figure 13] 1 is an SEM image of granules contained in Powder 4A of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, a numerical range expressed using "~" means a range that includes the numerical values ​​before and after "~" as the lower and upper limits.

[0010] [Aluminosilicate Granules] The aluminosilicate granules of the present invention contain nanotube particles and have pores with a diameter of more than 200 nm. Hereinafter, pores with a diameter of more than 200 nm are also referred to as "coarse pores". The aluminosilicate granules preferably contain nanotube particles as primary particles. The aluminosilicate granules are not particularly limited as long as they contain nanotube particles, and may contain other particles. The content of the nanotube particles in the aluminosilicate granules is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more, based on the total mass of the aluminosilicate granules. The upper limit of the content of the nanotube particles is not particularly limited, and may be 100 mass% based on the total mass of the aluminosilicate granules. In other words, the aluminosilicate granules may be granules formed by an aggregation of nanotube particles.

[0011] The shape of the aluminosilicate granules of the present invention is not particularly limited, and examples thereof include spherical, semispherical, spheroidal, ellipsoidal, plate-like, nodular, cylindrical, and polygonal prism-like shapes. The shape of the aluminosilicate granules of the present invention may be irregular. The particle size of the aluminosilicate granules of the present invention is not particularly limited and may be appropriately selected depending on the application, but is, for example, 0.5 to 200 μm, and preferably 1 to 100 μm. In this specification, the particle size of the aluminosilicate granules refers to the maximum size of the aluminosilicate granules, and is obtained by analyzing an image obtained by observing the aluminosilicate granules with a scanning electron microscope (SEM). In this specification, observation by SEM is performed using Sigma500 manufactured by Carl Zeiss Microscopy Ltd. When observing aluminosilicate granules by SEM, a powder containing the aluminosilicate granules of the present invention is attached to the adhesive surface of carbon tape, and a conductive coating is applied to the observation sample.

[0012] In the aluminosilicate granules of the present invention, the molar ratio of the SiO2 content to the Al2O3 content (hereinafter, simply referred to as "SiO2 / Al2O3") is not particularly limited, but is preferably 1.8 or more. In addition, SiO2 / Al2O3 is also preferably 2.1 or more, and may be 3.0 or more, or may be 5.0 or more. The upper limit of SiO2 / Al2O3 is not particularly limited, and examples thereof include 10,000 or less and 1,000 or less, preferably 500 or less, more preferably 300 or less, and even more preferably 200 or less. The SiO2 / Al2O3 is determined by X-ray fluorescence (XRF) analysis, and a powder containing the aluminosilicate granules of the present invention is used for the measurement. The SiO2 / Al2O3 obtained by measuring the powder is regarded as the SiO2 / Al2O3 of the aluminosilicate granules of the present invention. Specifically, XRF analysis is performed under the following conditions to determine SiO2 / Al2O3. Equipment used: ZSX Primus IV (Rigaku) ·Pretreatment method: Glass bead method using Li2B4O7 flux Quantitative method: Refractory Technology Association's standard sample for X-ray fluorescence analysis (clay brick standard sample series) and calibration curve method using other reagents

[0013] The nanotube particles contained in the aluminosilicate granules will be described below.

[0014] <Nanotube particles> The nanotube particles are not particularly limited, but are preferably nanotube particles containing an alumina component and a silica component, and more preferably nanotube aluminosilicate particles. The nanotube particles preferably contain particles derived from halloysite nanotubes, which will be described later. The aluminosilicate granules may contain two or more kinds of nanotube particles.

[0015] Halloysite is a clay mineral expressed as Al2Si2O5(OH)4·2H2O or Al2Si2O5(OH)4. That is, the SiO2 / Al2O3 ratio in halloysite is generally 2.0. Halloysite generally exhibits a variety of shapes, such as tubular (hollow tubular), spherical, angular nodules, plates, and sheets. The inner diameter (diameter of the tube hole) of the halloysite nanotube, which is a tubular (hollow tubular) halloysite, is, for example, about 10 to 20 nm. It is generally said that the outer surface of the halloysite nanotube particle is mainly made of silicate (SiO2) and the inner surface is mainly made of alumina (Al2O3).

[0016] In addition, particles derived from halloysite nanotubes are a concept that includes halloysite nanotube particles and particles obtained by subjecting halloysite nanotube particles to the treatment described below (hereinafter also referred to as "modified halloysite nanotube particles"). Examples of modified halloysite nanotube particles include metahalloysite nanotube particles obtained by calcining halloysite, and acid-treated metahalloysite nanotube particles obtained by subjecting metahalloysite nanotube particles to an acid treatment. The aluminosilicate granules may contain only halloysite nanotube particles, may contain only modified halloysite nanotube particles, may contain halloysite nanotube particles and modified halloysite nanotube particles, or may contain two or more types of modified halloysite nanotube particles.

[0017] The metahalloysite nanotube particles that may be contained in the above-mentioned aluminosilicate granules refer to nanotube-shaped halloysite in which the OH of halloysite represented by Al2Si2O5(OH)4 has been dehydrated to give a low crystallinity, and metahalloysite has traditionally been used commonly or conventionally as a term representing a variant of halloysite. The metahalloysite nanotube particles are obtained by firing the halloysite nanotube particles at a predetermined temperature. The predetermined temperature is preferably 500° C. or higher, more preferably 600° C. or higher. The upper limit of the predetermined temperature is preferably 925° C. or lower, more preferably 900° C. or lower.

[0018] The acid-treated metahalloysite nanotube particles that can be contained in the above-mentioned aluminosilicate granules are obtained by subjecting metahalloysite nanotube particles to an acid treatment. The acid treatment refers to a treatment in which an acid treatment solution is brought into contact with metahalloysite nanotube particles. The acid treatment leaches Al2O3 in the metahalloysite nanotube particles. Acid-treated metahalloysite nanotube particles often have pores with a diameter of 8 nm or less, and have unique adsorption properties derived from these pores. The acid-treated metahalloysite nanotube particles may be those which have been subjected to a calcination treatment after the acid treatment.

[0019] The characteristics of the aluminosilicate granules of the present invention will now be described.

[0020] <Coarse hole> The aluminosilicate granules of the present invention have pores with a pore size of more than 200 nm (coarse pores). The presence or absence of coarse pores can be confirmed by observing the surface of the aluminosilicate granules with an SEM (see FIG. 1). In this specification, the diameter of the coarse pores is the diameter of the pores that can be observed from the surface of the aluminosilicate granules when the surface is observed with an SEM. When the shape of the observed pores is not a perfect circle, the major axis of the longest distance between two parallel lines tangent to the shape of the pores is taken as the diameter of the coarse pores. The shape of the coarse pores observed under SEM is not particularly limited, and may be circular, elliptical, or another shape. In addition, when the distance between two parallel lines tangent to the shape of the pore is the shortest, the ratio of the pore diameter (long diameter) of the coarse pore to the short diameter is preferably 50 or less, more preferably 20 or less, may be 10 or less, 5 or less, or may be 2 or less. The ratio of the pore diameter (long diameter) of the coarse pore to the short diameter may be 1.

[0021] The diameter of the coarse pores is preferably 0.3 μm or more, more preferably 0.5 μm or more. The upper limit of the diameter of the coarse pores is not particularly limited, but is often 10 μm or less, preferably 5 μm or less. The pore size of the coarse pores is often 99% or less, preferably 90% or less, or may be 70% or less of the diameter (maximum diameter) of the aluminosilicate granules. The pore size of the coarse pores is often 1% or more, may be 5% or more, 10% or more, or may be 30% or more of the diameter (maximum diameter) of the aluminosilicate granules.

[0022] In the present invention, one aluminosilicate granule may have only one coarse pore, or may have multiple coarse pores. Note that the coarse pores may be mutually connected inside the aluminosilicate granule, or may be mutually independent. The pore size and structure of the coarse pores can be adjusted by the procedure in the powder production method described later. Furthermore, when the aluminosilicate granule has a plurality of coarse pores, the pore size of the coarse pore refers to the pore size of the coarse pore that is the largest pore size.

[0023] Pores with a diameter of more than 200 nm (coarse pores) are believed to contribute to the promotion of adsorption and reaction of solid substances because they enable the adsorption of large objects. For example, the presence of coarse pores makes it possible to capture dust, viruses, bacteria, pollen, etc. and react with them (for example, inactivate them). In addition, pores with a diameter of more than 200 nm have excellent mass transfer properties and can promote mass transfer when applied to various applications. For example, the aluminosilicate granules of the present invention have excellent mass transfer properties when used as a catalyst, catalyst carrier, adsorbent, sustained release material, etc.

[0024] <Pore> The aluminosilicate granules of the present invention preferably have fine pores other than the above-mentioned coarse pores. The pores preferably have a pore diameter of more than 8 nm and not more than 200 nm, more preferably more than 8 nm and not more than 100 nm. The presence or absence of pores can be confirmed by measuring an adsorption isotherm. Specifically, a nitrogen adsorption isotherm of a powder containing the aluminosilicate granules of the present invention is obtained, and the nitrogen adsorption isotherm is analyzed by the BJH (Barrett-Joyner-Halenda) method to create a plot (Log differential pore volume distribution) with pore diameter on the horizontal axis and differential pore volume on the vertical axis, thereby confirming the presence or absence of pores in the above pore diameter range. The measurement conditions for obtaining the nitrogen adsorption isotherm will be described in detail in the Examples section below. The same applies to the other measurement conditions below.

[0025] In addition, the aluminosilicate granule of the present invention preferably has a first pore derived from the nanotube-shaped particle and a second pore different from the first pore. The first pore preferably corresponds to the tube pore of the nanotube-shaped particle. The second pore preferably corresponds to the interparticle void of the nanotube-shaped particle contained in the aluminosilicate granule. The pore diameters of the first pore and the second pore are preferably both in the range of more than 8 nm and not more than 200 nm, more preferably both in the range of more than 8 nm and not more than 100 nm, and even more preferably both in the range of 10 to 50 nm. The first pore is preferably in the range of 10 to 20 nm. It is also preferable that the Log differential pore volume distribution analyzed by the BJH method shows two or more pore diameter peaks in the above range. The presence or absence of pores having a pore size of more than 8 nm and not more than 200 nm (more preferably more than 8 nm and not more than 100 nm) and the presence or absence of the first pores and the second pores can also be confirmed by observing the aluminosilicate granules with an SEM. When the surface of the aluminosilicate granule is observed by SEM, the presence of the first pores derived from the tube structure of the nanotube particles can be confirmed, and when the cross section of the aluminosilicate granule is observed by SEM, the presence of the second pores can be confirmed. For example, the cross section of the aluminosilicate granule can be observed by cutting the aluminosilicate granule with a focused ion beam (FIB) to obtain a sample and then observing the sample.

[0026] The aluminosilicate granules of the present invention may have third pores having a pore size of 8 nm or less, different from the first pores and the second pores. The aluminosilicate granules of the present invention may have third pores having a pore size of 8 nm or less, together with the pores having a pore size of more than 8 nm and less than 200 nm. The aluminosilicate granules of the present invention may also have the first pores having a pore size of more than 8 nm and less than 200 nm, the second pores having a pore size of more than 8 nm and less than 200 nm, and the third pores having a pore size of 8 nm or less. The presence or absence of third pores with a pore size of 8 nm or less can be confirmed by performing a so-called t-plot analysis of the nitrogen adsorption isotherm of a powder containing the aluminosilicate granules of the present invention to confirm the presence or absence of micropores with a size of less than 2 nm, or by fitting the nitrogen adsorption isotherm using the GCMC (Grand canonical Monte Carlo) method to obtain a pore size distribution. The third pores having a pore size of 8 nm or less are, for example, possessed by acid-treated metahalloysite nanotube particles, so that, for example, when an aluminosilicate granule contains an acid-treated metahalloysite nanotube particle, the aluminosilicate granule has a third pore having a pore size of 8 nm or less. Note that general halloysite nanotube particles do not have a third pore having a pore size of 8 nm or less. The third pores having a pore diameter of 8 nm or less are preferably, for example, 0.6 to 5 nm. The third pores having a pore diameter of 8 nm or less may have multiple peaks in the pore diameter range of 8 nm or less in the pore diameter distribution obtained by the above method.

[0027] The third pores having a pore size of 8 nm or less are nanospaces in a region close to the molecular size, and therefore can function as specific reaction sites and specific adsorption sites for molecules. When the aluminosilicate granules have third pores having a pore size of 8 nm or less, the aluminosilicate granules of the present invention can be suitably used as, for example, a catalyst, a catalyst carrier, an adsorbent, and the like.

[0028] In addition, the pores having a pore diameter of more than 8 nm and not more than 200 nm are considered to have superior mass transfer properties compared to the third pores having a pore diameter of 8 nm or less, and contribute to rapid reaction and adsorption, and can be used for the same applications as those described above. Furthermore, by combining the third pores having a pore diameter of 8 nm or less, it is considered that better performance can be achieved. The first pores are derived from the pores of the nanotube particles and are considered to have a tubular structure of a certain length, so that they can be expected to function as a catalyst having shape selectivity that selectively acts on the shape of molecules, etc. In addition, albumin can be placed in the pores of the above region to impart catalytic activity, which can be used for the synthesis of pharmaceuticals, etc. In addition, the pores in the above region can cause molecular adsorption accompanied by liquefaction due to capillary condensation, and can exhibit a large amount of adsorption, and therefore can function as an adsorbent (e.g., a moisture absorbent) that repeatedly adsorbs and desorbs, as well as a sustained-release material, etc.

[0029] Furthermore, the aluminosilicate granules of the present invention may simultaneously have a third pore with a pore size of 8 nm or less, and a pore size of more than 8 nm and less than 200 nm, and may also have pores with a pore size of more than 200 nm. The aluminosilicate granules of the present invention having both of the above-mentioned pores have a novel multimodal nanospace structure, and such a nanospace structure is expected to promote unexplored chemical reactions and has the potential to open up new technologies in the fields of the environment, energy, food, medicine, etc.

[0030] The above-mentioned advantages of having pores are merely examples, and it goes without saying that the aluminosilicate of the present invention can be used in general applications as a porous material. The formation of each of the above pores and the adjustment of each of the pores can be adjusted by the procedure and conditions of the production method described later.

[0031] <Other components and other particles> The aluminosilicate granules of the present invention may contain components other than the nanotube particles. For example, the aluminosilicate granules may contain a catalytic component that drives a desired reaction. The catalytic component may be supported on the aluminosilicate granules or nanotubular particles as particles, or as clusters of single atoms or a few atoms. The catalytic component may also be supported on the aluminosilicate granules and nanotubular particles. The elements contained in the catalyst component are not particularly limited and can be selected according to the desired reaction. Examples of elements contained in the catalyst component include Group 1 elements to Group 17 elements, and often contain transition metal elements or rare earth elements. The type of element contained in the catalyst component may be one type, or two or more types. The above-mentioned catalyst component is a concept that includes not only a catalyst component that advances a desired reaction, but also a so-called co-catalyst that promotes the progress of the desired reaction. The catalyst component may be a known one, and the catalyst component may be supported by a known method.

[0032] In the powder of the present invention, the aluminosilicate granules may contain a medicinal ingredient as a component other than the nanotube particles. The medicinal component is not particularly limited, and examples thereof include known deodorant components, antibacterial components, germicidal components, and pharmaceutical components.

[0033] The aluminosilicate granules may contain particles (other particles) other than the nanotube particles. The other particles are not particularly limited, and examples thereof include magnetic particles, coloring material particles, drug particles, etc. When the aluminosilicate granules contain magnetic particles, the aluminosilicate granules can be separated from the dispersion liquid by magnetic force.

[0034] <Powder characteristics> The breaking strength of the aluminosilicate granules is preferably 3 MPa or more. When the aluminosilicate granules of the present invention have the breaking strength, the coarse pores and the second pores are particularly likely to be maintained. Therefore, when the aluminosilicate granules of the present invention have the breaking strength, they are not easily broken during handling of the powder containing the aluminosilicate granules of the present invention, during pretreatment operations (e.g., dispersion treatment), and during composite treatment (e.g., kneading with resin), and the like, and the pores can be maintained. On the other hand, the breaking strength of the particles of general porous materials such as so-called silica gel, mesoporous silica, and activated carbon is often small, and the particles are broken during the above operations, etc., and the pore structure may not be maintained. The breaking strength is more preferably 4 MPa or more, and further preferably 5 MPa or more. The upper limit of the breaking strength is not particularly limited, and is, for example, 60 MPa or less, preferably 50 MPa or less, and more preferably 45 MPa or less.

[0035] The breaking strength of the aluminosilicate granules of the present invention is measured by a compression test using a micro compression tester, and is the average value of five test results. More specifically, the aluminosilicate granules of the present invention are first used as a sample. A very small amount of this sample is scattered on the sample stage (lower pressure plate) of a micro-compression tester MCT-510 (manufactured by Shimadzu Corporation), and a compression test is performed on each sample grain to determine the breaking strength. Usually, the average value of five test results (breaking strength) is taken as the breaking strength of the powder. The breaking strength is calculated by measuring the diameters of each sample particle in the X and Y directions on the sample stage, taking the average value as the particle size of each sample particle, and using the following formula (1). (1) Cs = 2.48 × P / (πd 2 ) In formula (1), Cs is the breaking strength (unit: MPa), P is the breaking test force (unit: N), and d is the diameter of the sample particle (unit: mm).

[0036] It is also preferable that the hydrated breaking strength of the aluminosilicate granules hydrated by immersing in pure water for 24 hours is 80% or more of the above breaking strength. The hydrated breaking strength may be the same value as the above breaking strength, i.e., 100%. When the hydrated breaking strength is excellent, the pore structure is easily maintained even in applications where the granules come into contact with aqueous solutions, etc., which is preferable. The wet fracture strength is measured in the same manner as in the above-mentioned method for measuring fracture strength, except that the sample is aluminosilicate granules that have been immersed in pure water for 24 hours to become wet.

[0037] [Powder] The powder of the present invention comprises the aluminosilicate granules of the present invention described above. It is also preferable that the powder of the present invention has a ratio of the number of aluminosilicate granules having coarse pores of 1% or more when an observation sample is obtained by the above-mentioned method and observed by SEM to obtain an observation image. The ratio of the number of aluminosilicate granules having coarse pores may be 5% or more, 10% or more, or 50% or more. The ratio of the number of aluminosilicate granules having coarse pores may be 100% or less, 90% or less, or 70% or less. The proportion of the aluminosilicate granules having the coarse pores is calculated by the following procedure. First, in the observation image, the number of particles whose overall shape can be confirmed and whose overall shape can be adequately estimated are counted. The number of particles to be counted is 200 or more. If the number of particles counted in one observation image is less than 200, the above particle count is also performed in observation images obtained in other fields of view, and the counting is continued until the number of particles counted reaches 200 or more. At this time, the ratio of the number of particles in which coarse pores are found among the counted particles is regarded as the ratio of the number of aluminosilicate granules having coarse pores. The proportion of the number of aluminosilicate granules having coarse pores calculated by the above method can be adjusted, for example, by the conditions of the production method described later.

[0038] The content of the aluminosilicate granules is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 5% by mass or more, and may be 10% by mass or more, 50% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more, based on the total mass of the powder of the present invention. The upper limit of the content of the aluminosilicate granules in the powder of the present invention is not particularly limited, and may be 100% by mass based on the total mass of the powder. That is, the powder of the present invention may be composed of the aluminosilicate granules of the present invention. The powder of the present invention may also contain aluminosilicate granules that do not have coarse pores. When the powder of the present invention contains aluminosilicate granules that do not have coarse pores, the content of the aluminosilicate granules that have coarse pores is preferably 1% by mass or more, more preferably 5% by mass or more, may be 10% by mass or more, may be 50% by mass or more, or may be 70% by mass or more, based on the total mass of the aluminosilicate contained in the powder of the present invention. The upper limit of the content of the aluminosilicate granules that have coarse pores in the powder of the present invention is not particularly limited, and may be 100% by mass based on the total mass of the powder. That is, the powder of the present invention may be composed of aluminosilicate granules that have coarse pores.

[0039] The characteristics of the powder of the present invention will now be described.

[0040] <Specific surface area> The specific surface area (BET specific surface area) of the powder of the present invention is 30 m 2 / g or more is preferable, and 50m 2 / g or more is more preferable. Also, the BET specific surface area is 80m 2 The upper limit of the BET specific surface area is not particularly limited, but may be, for example, 1000 m 2 / g or less, and 600m 2 / g or less. The BET specific surface area is usually 200m 2 / g or less. The BET specific surface area can be determined by applying the BET method to a nitrogen adsorption isotherm.

[0041] <Pore volume> The total pore volume of the powder of the present invention is 0.20 cm 3 / g or more is preferable, and 0.23 cm 3 / g or more is more preferable. The total pore volume is 0.45 cm 3 The upper limit of the total pore volume is not particularly limited, but may be, for example, 2.00 cm 3 / g or less, and 1.20 cm 3 / g or less. The total pore volume is usually 0.80 cm 3 / g or less. The total pore volume is calculated from the adsorption amount at a relative pressure of 0.99 from the nitrogen adsorption isotherm using the following formula. Vp = V / 22414 × Mg / ρg Vp: total pore volume up to relative pressure (0.99) V: Adsorption amount at relative pressure (0.99) 22414:Volume of gas per mole Mg: Molecular weight of adsorbate (N2) (28.013) ρg: Density of the adsorbate (N2) (0.808)

[0042] In addition, when the powder of the present invention has micropores (less than 2 nm), the volume of the micropores is less than 0.01 cm 3 / g or more is preferable, and 0.02 cm 3 / g or more is more preferable, and 0.04 cm 3 / g or more is more preferable, and 0.08 cm 3 The upper limit of the volume of the micropores is not particularly limited, but is, for example, 0.5 cm 3 / g or less, and 0.2 cm 3 / g or less in most cases.

[0043] <Powder characteristics> The average particle size of the powder of the present invention is not particularly limited and may be appropriately selected depending on the application, but is, for example, 0.5 to 200 μm, preferably 1 to 100 μm. The powder of the present invention may be granulated before use. The size of the granulated powder is preferably 5 mm or less. The average particle size is measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Microtrac Bell.

[0044] [Powder applications] The powder of the present invention can be preferably used, for example, as an adsorbent. Furthermore, the powder of the present invention is not limited to use as an adsorbent, but can be applied to a wide variety of applications. Examples of uses include catalysts, catalyst carriers, humidity conditioners, sustained-release materials, cosmetics, colorants, precision polishing particles, magnetic materials, deodorants, antibacterial agents, water purification agents, colorants, foods, fermentation, pharmaceuticals, and artificial enzymes, but needless to say, the uses are not limited to these. The powder of the present invention is also suitable as a filler imparting properties such as light weight, heat insulation or sound absorption, and as a coating material.

[0045] [Powder manufacturing method] A method for producing the powder of the present invention (hereinafter, for convenience, also referred to as the "production method of the present invention") will be described. According to the production method of the present invention, a powder containing the above-mentioned aluminosilicate granules of the present invention can be obtained. The manufacturing method of the present invention preferably includes at least a step of preparing a slurry containing nanotube particles and template particles (described later) (slurry preparation step), a step of preparing a template-containing powder from the slurry (powder preparation step), and a template removal step of removing the template particles from the template-containing powder, thereby obtaining a powder containing aluminosilicate granules having coarse pores, the aluminosilicate granules being formed by the aggregation of nanotube particles. Hereinafter, a preferred embodiment of the production method of the present invention in which the nanotube particles include halloysite nanotube particles will be described.

[0046] <Slurry preparation process> (Raw material (Halloysite)) As the raw material halloysite used in the manufacturing method of the present invention (hereinafter also referred to as "raw material halloysite"), commercially available halloysite (halloysite nanotubes) can be used, and specifically, for example, halloysite manufactured by APPLIED MINERALS (product name: DRAGONITE-HP) can be suitably mentioned.

[0047] (Slurrying) First, a slurry in which the raw halloysite is dispersed in water is obtained. The method for dispersing the raw halloysite in water is not particularly limited, and for example, a conventionally known device such as a high-speed mixer, a disperser, a bead mill, or a homomixer can be used. The solid content concentration of the slurry is not particularly limited and is, for example, 30 to 50 mass %.

[0048] It is preferable to add a dispersant to the slurry because it is closely related to the accuracy of the centrifugation described later. By adding a dispersant, a slurry with a higher concentration can be obtained, which also has the effect of improving the productivity in drying using a spray dryer or the like described later.

[0049] The dispersant is preferably one that can provide a stable slurry with a small amount of use, and examples thereof include polymer-type anionic surfactants (anionic polymer surfactants). Specific examples of anionic polymer surfactants include special polycarboxylic acid type Poise 520, 521, and 530 (all manufactured by Kao Corporation). Depending on the intended use, Poise 532A, Caocera 2000, 2020 and 2110 (ibid.), which do not contain metal ions such as sodium and potassium, can also be used. Furthermore, the anionic polymer surfactant is not limited to the polycarboxylic acid type, and acrylic acid type, sulfonic acid type, etc. can also be used.

[0050] The content of the dispersant is not particularly limited, but a suitable example is 0.5 to 3.0 mass % based on the total solid content in the slurry. If the dispersant content is too low, the dispersion of halloysite and impurity particles in the slurry may be insufficient. On the other hand, if the dispersant content is too high, it may cause agglomeration or increase costs. Furthermore, it may be prone to problems in downstream processes (such as a decrease in the recovery rate of the dispersed phase during centrifugation, insufficient drying during spray drying, or insufficient caking or burning during firing).

[0051] (coarse grain removal) In order to increase the accuracy of the centrifugation described later, coarse particles in the slurry may be removed. For example, a sieve with 25 to 100 μm openings or a wet cyclone may be used to remove the coarse particles. Alternatively, the slurry may be allowed to settle and separate to remove the coarse particles.

[0052] (Centrifugation) The obtained slurry is centrifuged to separate it into a lower sedimentation phase and an upper dispersed phase. The sedimentation phase contains many impurities such as fine sand, and the dispersed phase contains many halloysite nanotube particles. The solid content of the dispersed phase (slurry) is, for example, 10 to 30% by mass. The centrifugal force and processing time during centrifugation are, for example, 2000 to 3000 G and 3 to 30 minutes, respectively, but are not limited to these values ​​and are appropriately set in consideration of the dispersion state, application, cost, and the like. Larger centrifuges can also be used for mass production. By recovering the dispersed phase, the halloysite nanotube particles can be purified and separated from the raw halloysite containing impurities such as fine sand.

[0053] (Addition of template particles) The template particles are added to the collected dispersed phase (slurry). The amount of the template particles added is, for example, 2 to 50% by mass relative to the total amount of the halloysite nanotube particles and the template particles in the slurry after the addition, but is not limited thereto. After the addition, the template particles are dispersed in the slurry. The method for dispersing the template particles in the slurry is not particularly limited, and for example, a conventionally known device such as a high-speed mixer, a disperser, a bead mill, or a homomixer can be used. The slurry obtained in the slurry preparation step may be subjected to operations such as purification, classification, magnetic separation, and concentration, if necessary.

[0054] The template particles are composed of a material that is removable in a template removal step. Examples of the template particles include resin particles and carbon particles that can be removed by a baking treatment described later, and examples of the template particles include magnesium oxide particles, calcium carbonate particles, and zinc oxide particles that can be removed by an acid treatment described later. The template particles are not limited to the above examples, and may be any particles that can be removed in the template removal step.

[0055] The particle size and shape of the template particles can be appropriately selected depending on the desired pore size and shape of the coarse pores. The content of the template particles in the slurry can be appropriately adjusted depending on the desired number of coarse pores. The shape of the template particle may be, for example, a sphere, a plate, a rod, a polygonal pyramid, etc. The particle diameter of the template particle may be, for example, more than 0.1 μm and not more than 5 μm, and may be more than 0.2 μm and not more than 5 μm. Only one type of template particle may be used, or two or more types may be used.

[0056] The template particles may be subjected to a surface treatment in order to control the dispersibility in the slurry, for example, a hydrophilic treatment or a hydrophobic treatment. By subjecting the template particles to a surface treatment, the distribution of the template particles in the granules obtained in the powder preparation step described below can be changed, making it possible to control the shape and distribution of the coarse pores in the final powder (aluminosilicate granules).

[0057] <Powder preparation process> The powder preparation step is a step of preparing a template-containing powder from the slurry prepared in the slurry preparation step. The template-containing powder includes aluminosilicate granules including template particles and halloysite nanotube particles. The mold-containing powder obtained in the powder preparation step may be further granulated by subjecting it to treatments such as rolling, stirring, extrusion, etc. This allows the size of the granules constituting the mold-containing powder to be increased.

[0058] (Spray drying) The powder preparation step may, for example, be a step of obtaining a mold-containing powder by spray drying the slurry prepared in the slurry preparation step.

[0059] To spray-dry the prepared slurry, a spray dryer is used, which is a device that sprays (atomises) the liquid raw material into fine droplets and dries them with hot air to instantly obtain powder. The spray dryer is a conventionally known device, and examples of the spray dryer include spray dryers manufactured by Okawara Kakoki Co., Ltd., Fujisaki Electric Co., Ltd., and Nippon Kagaku Kikai Seizo Co., Ltd. In a spray dryer, the particle size of the powder particles (granules) obtained by drying can be controlled by changing the size of the droplets obtained by spraying (atomizing) the liquid raw material. The method of atomizing the liquid raw material using a spray dryer is not particularly limited, and a conventionally known method such as a two-fluid nozzle method, a pressure nozzle (pressurized nozzle) method, a four-fluid nozzle method (twin jet nozzle method), or a rotating disk method can be appropriately selected depending on the desired droplet size. Since the particle size of the powder particles (granules) obtained by drying varies depending on the concentration of the slurry and / or the processing amount, in order to obtain the desired particle size, in addition to the atomization method, the state of the slurry must be appropriately selected. The contact method between the hot air and the sprayed droplets can be appropriately selected from the following types: a general parallel flow type in which the hot air and sprayed droplets both flow downward; a counter flow type in which the hot air flows upward in a counterflow direction while the sprayed droplets flow downward; and a parallel counter flow type in which the sprayed droplets flow upward and the hot air flows downward.

[0060] Spray drying applies heat instantaneously, so the powder itself does not easily become hot. Spray drying dries the slurry to obtain powder directly, so there is no need for processes such as filtration, drying, and pulverization, and contamination that may occur during these steps can be suppressed.

[0061] The above describes the method of obtaining the mold-containing powder by the spray drying process. On the other hand, as mentioned above, the method of obtaining the mold-containing powder is not particularly limited, and may be, for example, a method of using the above-mentioned slurry by medium fluidized drying (ball-containing fluidized bed drying). In the medium fluidized drying, the slurry to be dried is first continuously fed to a layer of ceramic balls of 1 to 3 mm diameter in a fluidized state, so that the slurry adheres to the ball surfaces. The material to be dried is instantly dried by heat conduction from the heated balls and convection heat transfer from the fluidized hot air, and is peeled off from the ball surfaces by collision between the balls. In this way, a mold-containing powder is obtained.

[0062] By adjusting the procedure and conditions for obtaining the mold-containing powder, the particle size and shape of the granules in the obtained powder can be adjusted. In addition, by adjusting the procedure and conditions for obtaining the mold-containing powder, the amount and distribution of the mold particles in the granules contained in the mold-containing powder can be changed, and the structure of the coarse pores in the finally obtained aluminosilicate granules can be adjusted. Furthermore, adjusting the template particles used may contribute to the formation of the second pores described above.

[0063] <Mold removal process> The mold removal step is a step of removing mold particles from the aluminosilicate granules contained in the mold-containing powder. When the mold particles are removed, coarse pores are formed in the aluminosilicate granules according to the shape and distribution of the mold particles. The treatment carried out in the template removal step can be appropriately selected depending on the material of the template particles. Examples of the treatment carried out in the template removal step include a firing treatment and an acid treatment. The firing treatment and the acid treatment are described below.

[0064] (Firing treatment) When resin particles, carbon particles, or the like are used as the template particles, the template particles can be removed by a baking treatment. The firing temperature, firing atmosphere and firing time in the firing treatment are not particularly limited as long as the template particles can be removed, and can be appropriately adjusted. The firing temperature is preferably 200° C. or higher, more preferably 300° C. or higher, and even more preferably 400° C. or higher. On the other hand, the firing temperature is preferably 1000° C. or lower, more preferably 900° C. or lower, and even more preferably 800° C. or lower. The firing time is preferably 0.5 hours or more, more preferably 0.75 hours or more, while the firing time is preferably 10 hours or less, more preferably 5 hours or less.

[0065] The firing atmosphere is not particularly limited, and may be, for example, an air atmosphere. When the template particles are resin particles, carbon particles, or the like, it is also preferable to use a firing atmosphere having a higher oxygen content than the air atmosphere.

[0066] The calcination treatment may cause the halloysite nanotube particles contained in the granules to change into metahalloysite nanotube particles.

[0067] (Acid treatment) When magnesium oxide particles, calcium carbonate particles, zinc oxide particles, or the like are used as the template particles, the template particles can be removed by an acid treatment. The acid treatment refers to a treatment in which the mold-containing powder is brought into contact with an acid treatment liquid, which is preferably a liquid containing water and an acidic component. The acid treatment liquid may be a conventionally known acid aqueous solution, for example, inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid, and organic acids such as oxalic acid and acetic acid. The acid treatment liquid may contain two or more acids. That is, the acid treatment liquid may be a mixed acid. The concentration of the acid in the acid treatment solution is not particularly limited as long as the template particles can be removed, but from the viewpoint of shortening the time of the acid treatment, it is preferably 0.1 mol / L or more, more preferably 1.0 mol / L or more, and even more preferably 2.0 mol / L or more. The upper limit of the acid treatment solution is not particularly limited, but it may be, for example, 12.0 mol / L or less. The type of acid contained in the acidic treatment solution can be appropriately selected depending on the desired physical properties, cost, and the like. In addition, it is preferable to select materials that are resistant to corrosion by the acid contained in the acid treatment solution for the parts of the equipment for carrying out the acid treatment that may come into contact with the acid treatment solution.

[0068] In the acid treatment, the method of contacting the mold-containing powder with the acid treatment liquid includes, for example, placing the mold-containing powder in the acid treatment liquid and stirring the acid treatment liquid. The stirring method is not particularly limited, and for example, the acid treatment liquid and the mold-containing powder may be placed in a tank equipped with a stirring blade and stirred. The ratio of the mass of the acid treatment liquid to the mass of the mold-containing powder can be appropriately set, but is, for example, 5 to 100, and 10 to 50 is preferable. The temperature of the acid treatment solution during the acid treatment can be appropriately set, for example, to 10 to 100°C, and preferably 20 to 90°C. The time for the acid treatment can be adjusted appropriately depending on the type of mold particles contained in the mold-containing powder, the type of acid treatment liquid used, the ratio of the mass of the acid treatment liquid to the mass of the mold-containing powder, and the temperature of the acid treatment liquid, and can be, for example, 10 minutes to 48 hours, with 30 minutes to 12 hours being preferred.

[0069] <Other processes> The method for producing halloysite powder of the present invention may further include other steps in addition to the above steps.

[0070] For example, when an acid treatment is carried out as the template removal step, a pre-calcination step may be carried out before carrying out the acid treatment. The pre-calcination step may be carried out in the same manner as the above-mentioned calcination treatment. The calcination temperature in the pre-calcination step is preferably 600 to 900°C. When calcination is carried out within the above-mentioned preferred temperature range, the halloysite nanotube particles contained in the aluminosilicate granules become metahalloysite nanotube particles. When the acid treatment is performed after the pre-calcination step, the metahalloysite nanotube particles are also subjected to the acid treatment, and aluminosilicate granules containing acid-treated metahalloysite nanotube particles are obtained. As described above, the acid-treated metahalloysite nanotube particles often have third pores with a pore size of 8 nm or less, and the obtained powder can be given properties derived from the above pores. Furthermore, the powder obtained by carrying out the pre-calcination step and the acid treatment may be further subjected to a calcination treatment. The calcination temperature in the post-calcination step is preferably more than 200° C. and not more than 1100° C., more preferably 300 to 1000° C. By carrying out the further calcination treatment, the physical properties of the powder can be controlled.

[0071] In addition, when a calcination treatment is performed as the template removal step, the above-mentioned acid treatment may be further performed after the calcination treatment. When the temperature in the calcination treatment as the template removal step is, for example, 600 to 900°C, the halloysite nanotube particles contained in the aluminosilicate granules become metahalloysite nanotube particles, and the acid treatment produces aluminosilicate granules containing acid-treated metahalloysite nanotube particles. Furthermore, the powder obtained by the acid treatment may be subjected to the post-calcination step described above. The post-baking step and the acid treatment may be carried out repeatedly.

[0072] The method for producing a powder of the present invention may include a step of washing the obtained powder (washing step). The washing step is also preferably carried out between the acid treatment step and the post-calcination step described below. The washing step makes it possible to remove the acid treatment liquid and the like from the obtained powder. The washing step is preferably a step of contacting the obtained powder with a washing liquid. The washing liquid may be, for example, water. As the water, pure water (e.g., ion-exchanged water) may be used.

[0073] The method for contacting the obtained powder with the washing liquid may be the same as that for the acid treatment step. After contacting with the washing liquid, the powder is separated from the washing liquid. The separation method is not particularly limited, and any known method can be applied, for example, sedimentation separation, filtration separation, and the like. Sedimentation separation utilizes gravity or centrifugal force to separate liquid and powder due to the difference in specific gravity. In filtration separation, the powder is separated from the liquid by trapping the powder in a filter or the like and passing the liquid through the filter. Filtration separation may be dead-end filtration or cross-flow filtration.

[0074] The washing step may be carried out repeatedly. For example, after the powder is separated from the washing liquid by the above method, the separated powder is again brought into contact with the washing liquid and the washing step is repeated. The washing step may be repeated, for example, until the conductivity of the filtrate reaches a predetermined level.

[0075] The powder obtained by the washing step may be subjected to a drying treatment. The drying method is not particularly limited, and any known method can be applied. The drying temperature is usually 200° C. or lower.

[0076] <Specific examples of powder manufacturing methods> The method for producing the powder is as described above, and the steps described above may be carried out in the following order.

[0077] (Example 1) An example of adding resin particles that can be removed by a baking treatment to the slurry containing halloysite nanotube particles in the above-mentioned slurry preparation step will be described. When the slurry containing the resin particles is subjected to spray drying, which is a powder preparation step, aluminosilicate granules containing halloysite nanotube particles and resin particles are obtained. When the aluminosilicate granules containing the halloysite nanotube particles and the resin particles are subjected to a baking treatment, which is a template removal step, the resin particles disappear and pores (coarse pores) corresponding to the shape of the resin particles are formed. The aluminosilicate granules that have been subjected to the above-mentioned firing treatment have large pores, first pores derived from the nanotube particles, and second pores.

[0078] When the aluminosilicate granules are subjected to the above-mentioned firing treatment at a temperature of, for example, 600 to 900° C., the halloysite nanotube particles contained in the aluminosilicate granules are converted to metahalloysite nanotube particles. When the above-mentioned acid treatment is applied to aluminosilicate granules containing metahalloysite nanotube particles, acid-treated aluminosilicate granules containing metahalloysite nanotube particles are obtained. In addition, as mentioned above, the aluminosilicate granules containing the acid treated metahalloysite nanotube particles may be further subjected to a post-calcination step. The aluminosilicate granules containing acid-treated metahalloysite nanotube particles obtained by the above procedure have coarse pores, first pores derived from the nanotube particles, second pores, and third pores of 8 nm or less derived from the acid-treated metahalloysite nanotube particles.

[0079] (Example 2) An example of adding particles removable by acid treatment (calcium carbonate particles) to the slurry containing halloysite nanotube particles in the above-mentioned slurry preparation step will be described. When the slurry containing calcium carbonate particles is subjected to spray drying, which is a powder preparation step, aluminosilicate granules containing halloysite nanotube particles and calcium carbonate particles are obtained. When aluminosilicate granules containing halloysite nanotube particles and calcium carbonate particles are subjected to an acid treatment, which is a template removal step, the calcium carbonate particles disappear and pores (coarse pores) corresponding to the shape of the calcium carbonate particles are formed. The aluminosilicate granules that have been subjected to the acid treatment have large pores, first pores derived from the nanotube particles, and second pores.

[0080] The aluminosilicate granules subjected to the acid treatment may be further subjected to a calcination treatment. When the aluminosilicate granules are subjected to the above-mentioned firing treatment at a temperature of, for example, 600 to 900° C., the halloysite nanotube particles contained in the aluminosilicate granules are converted to metahalloysite nanotube particles. When the above-mentioned acid treatment is further applied to the aluminosilicate granules containing metahalloysite nanotube particles, acid-treated aluminosilicate granules containing metahalloysite nanotube particles are obtained. In addition, as mentioned above, the aluminosilicate granules containing the acid treated metahalloysite nanotube particles may be further subjected to a post-calcination step. The aluminosilicate granules containing acid-treated metahalloysite nanotube particles obtained by the above procedure have coarse pores, first pores derived from the nanotube particles, second pores, and third pores of 8 nm or less derived from the acid-treated metahalloysite nanotube particles.

[0081] (Example 3) Another example of adding particles removable by acid treatment (calcium carbonate particles) to the slurry containing halloysite nanotube particles in the above-mentioned slurry preparation step will be described. When the slurry containing calcium carbonate particles is subjected to spray drying, which is a powder preparation step, aluminosilicate granules containing halloysite nanotube particles and calcium carbonate particles are obtained. When the aluminosilicate granules containing halloysite nanotube particles and calcium carbonate particles are subjected to a firing treatment, the calcium carbonate particles are not removed, and the strength of the aluminosilicate granules is increased.

[0082] When the aluminosilicate granules that have been subjected to the above-mentioned calcination treatment are subjected to an acid treatment, which is a mold removal step, the calcium carbonate particles disappear and pores (coarse pores) corresponding to the shape of the calcium carbonate particles are formed. The aluminosilicate granules that have been subjected to the acid treatment have large pores, first pores derived from the nanotube particles, and second pores.

[0083] When the aluminosilicate granules are subjected to the above-mentioned firing treatment at a temperature of, for example, 600 to 900° C., the halloysite nanotube particles contained in the aluminosilicate granules are converted to metahalloysite nanotube particles at the same time as the calcium carbonate particles are removed. When the above-mentioned acid treatment is further applied to the aluminosilicate granules containing metahalloysite nanotube particles, acid-treated aluminosilicate granules containing metahalloysite nanotube particles are obtained. In addition, as mentioned above, the aluminosilicate granules containing the acid treated metahalloysite nanotube particles may be further subjected to a post-calcination step. The aluminosilicate granules containing acid-treated metahalloysite nanotube particles obtained by the above procedure have coarse pores, first pores derived from the nanotube particles, second pores, and third pores of 8 nm or less derived from the acid-treated metahalloysite nanotube particles.

[0084] (Example 4) An example will be described in which resin particles removable by firing treatment and particles removable by acid treatment (calcium carbonate particles) are added to the slurry containing halloysite nanotube particles in the above-mentioned slurry preparation step. When the slurry containing the resin particles and calcium carbonate particles is subjected to spray drying, which is a powder preparation step, aluminosilicate granules containing halloysite nanotube particles, resin particles and calcium carbonate particles are obtained. When aluminosilicate granules containing halloysite nanotube particles, resin particles, and calcium carbonate particles are subjected to a baking treatment, which is a mold removal step, the resin particles disappear and pores (coarse pores) corresponding to the shape of the resin particles are formed.

[0085] Furthermore, when the aluminosilicate granules that have been subjected to the above-mentioned firing treatment are subjected to an acid treatment, the calcium carbonate particles disappear and pores (coarse pores) corresponding to the shape of the calcium carbonate particles are formed. The aluminosilicate granules that have been subjected to the above-mentioned calcination treatment and acid treatment have large pores, first pores derived from the nanotube particles, and second pores.

[0086] In addition, when the aluminosilicate granules that have been subjected to the above-mentioned firing treatment are fired at, for example, 600 to 900°C, the halloysite nanotube particles are converted into metahalloysite nanotube particles, and therefore, by acid treatment, aluminosilicate granules containing acid-treated metahalloysite nanotube particles are obtained. The aluminosilicate granules containing acid-treated metahalloysite nanotube particles obtained by the above procedure have coarse pores, first pores derived from the nanotube particles, second pores, and third pores of 8 nm or less derived from the acid-treated metahalloysite nanotube particles.

[0087] In the procedure of Example 4, the acid treatment and the calcination treatment may be carried out in the reverse order. EXAMPLES

[0088] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples.

[0089] [Example 1] Powder 1, which corresponds to the powder of the present invention, was produced by the following procedure.

[0090] <Raw material halloysite> As the raw material halloysite, halloysite manufactured by APPLIED MINERALS (product name: DRAGONITE-HP) was prepared.

[0091] <Slurrying> Raw halloysite, water and anionic polymer surfactant (Kao Corporation, Poise 520) were placed in a high-speed mixer (Nihon Seiki Seisakusho, Ultra Homo Mixer UHM-20 (20 liters)) and processed at 10,000 rpm for 10 minutes to obtain a slurry (solid content concentration: 40% by mass) in which raw halloysite was dispersed in water. The content of the anionic polymer surfactant relative to the total solid content of the slurry was 1.5% by mass.

[0092] <Centrifugation> The slurry was centrifuged for 10 minutes at a centrifugal force of 2500G using a centrifuge (Kubota Shoji Co., Ltd., High-Speed, Large-Capacity Refrigerated Centrifuge 7000), separating the slurry into a precipitated phase and a dispersed phase, and the dispersed phase was collected. The solid content of the dispersed phase (slurry) of nanotubes from which impurities such as quartz and coarse particles had been removed was 24% by mass. The solid content was measured using a halogen heating moisture meter (Shinko Denshi Co., Ltd., MA-120) at a dry heat treatment temperature of 200°C.

[0093] <Addition of template particles> To 90 parts by mass of the solid content of the collected dispersed phase (slurry), 10 parts by mass of template particles (polymethyl methacrylate particles, average particle size: 2.5 μm, MBX-2H manufactured by Sekisui Chemical Co., Ltd.) were added. Furthermore, water was added to adjust the total solid content to 25% by mass, and the template particles were dispersed in the slurry by processing for 10 minutes at 8000 rpm using a high-speed mixer (Ultra Homo Mixer UHM-20 manufactured by Nippon Seiki Seisakusho Co., Ltd.).

[0094] <Spray drying> The dispersed phase (slurry) to which the template particles were added was spray-dried using a spray dryer to obtain a template-containing powder. The spray dryer used was an L-8i spray dryer manufactured by Okawara Kakoki Co., Ltd. The slurry was supplied at a fixed rate using a pump to atomize (spray) the slurry. The contact method between the hot air and the sprayed droplets was a parallel flow type in which both the hot air and the sprayed droplets flowed downward. The spray drying conditions are as follows: Atomization method: Rotating disk method Disk rotation speed: 25000RPM Water evaporation rate: 2.1kg / h ·Inlet temperature: 190℃ ·Outlet temperature: 80℃

[0095] <Mold removal process> The obtained mold-containing powder was subjected to a firing treatment in an air atmosphere to remove the mold particles. Specifically, the temperature was raised at 4° C. / min, the firing temperature was set to 650° C., and the firing time was set to 1 hour. The powder obtained by the above process is hereinafter also referred to as "powder 1."

[0096] <Evaluation of Powder 1> Powder 1 was evaluated by the following methods.

[0097] (SEM observation) Powder 1 was observed by SEM. The observed images are shown in Figures 1 and 2. Figure 2 is an enlarged image of Powder 1. As shown in FIG. 1, SEM observation confirmed that the aluminosilicate granules contained in Powder 1 had pores (coarse pores) with a pore size of more than 200 nm. In addition, from the SEM image shown in FIG. 2, it was confirmed that Powder 1 contains granules (aluminosilicate granules) formed by the aggregation of halloysite including halloysite nanotube particles. It was also confirmed that holes (first pores) originating from the tube pores of the halloysite nanotube particles exist on the surface of the granules. Furthermore, it was confirmed that holes (second pores) larger in diameter than the tube pores of the halloysite nanotube particles exist on the cross section of the granules (not shown). From the above results, it was confirmed that Powder 1 had coarse pores and pores derived from tube pores, and was a powder with a novel structure.

[0098] (Nitrogen adsorption isotherm) In the present invention, nitrogen adsorption isotherms were obtained under the following conditions and procedures, and various analyses were carried out. First, the powder was pretreated (vacuum degassing at 120°C for 8 hours), and then the adsorption and desorption isotherms with nitrogen were measured using a constant volume method under the following conditions. The equilibrium waiting time is the waiting time after the adsorption equilibrium state is reached. ·Adsorption temperature: 77K Cross section of nitrogen: 0.162nm 2 Saturated vapor pressure: Actual measurement Equilibration wait time: 500sec Pretreatment device: BELPREP-vacII (Microtrack, BEL) Measurement device: BELSORP-mini (Microtrack BEL) Analysis software: BELMaster Version 6.4.0.0 (Microtrack-Bell)

[0099] BET specific surface area [m 2 / g] was determined by applying the BET method to the nitrogen adsorption isotherm. The log differential pore volume distribution was calculated from the nitrogen adsorption isotherm by applying the BJH method using the FHH standard curve. The total pore volume was also calculated by the above method.

[0100] From the above measurements and analyses, the BET specific surface area and total pore volume of Powder 1 were as follows: ·BET specific surface area: 64.5m 2 / g Total pore volume: 0.44cm 3 / g

[0101] The nitrogen adsorption isotherm of Powder 1 was analyzed for pore size distribution by the BJH method. The results are shown in Figure 3. In each graph, the horizontal axis represents pore size [nm], and the vertical axis represents differential pore volume (dVp / dlogDp) [cm 3 In the graph of FIG. 3, two or more pore size peaks were confirmed within the range of 10 nm or more (more than 8 nm and 200 nm or less).

[0102] (Average particle size) The average particle size of Powder 1 was measured by the method described above and was found to be 25.3 μm.

[0103] (Antibacterial Test) A test (stirring method) was carried out to evaluate the antibacterial activity of Powder 1. Staphylococcus aureus (NBRC12732 strain) was used as the test strain. The specific procedure for the antibacterial test is as follows. First, 0.3 g of Powder 1 was weighed out and sterilized by dry heat at 160°C for 2 hours. The sterilized powder was added to 9.9 mL of sterile saline, and then 1.4 × 10 70.1 mL of a Staphylococcus aureus suspension was inoculated at CFU / mL. The physiological saline inoculated with the Staphylococcus aureus suspension was stored at 25°C while being rotary shaken at 200 rpm. The antibacterial activity of Powder 1 was evaluated by leaving it to stand for 10 minutes after the specified storage time had elapsed, allowing Powder 1 to settle, and then measuring the viable cell count by sampling 9.0 mL of the supernatant. A Staphylococcus aureus biological medium sheet (manufactured by JNC Corporation) was used to measure the viable cell count. The same test was also conducted in a container containing another physiological saline solution, for a total of three containers, and the antibacterial activity of Powder 1 was evaluated by the average of the viable cell counts. The data showing the transition of viable cell counts is shown in FIG. FIG. 4 also shows the change over time in viable cell count for a control run conducted under similar conditions except that Powder 1 was not added.

[0104] Furthermore, for comparison, powder 2 was obtained in the same manner as powder 1 except that the template particles were not added, and the same test was carried out (see FIG. 4). SEM images of powder 2 are shown in FIG. 5 and FIG. 6. FIG. 6 is an enlarged image of powder 2. From the observation image shown in Fig. 5, it was confirmed that the aluminosilicate granules contained in Powder 2 did not have pores (coarse pores) with a pore size of more than 200 nm. In addition, from the SEM image shown in Fig. 6, it was confirmed that Powder 2 contained granules (aluminosilicate granules) formed by aggregation of halloysite containing halloysite nanotube particles. The BET specific surface area and total pore volume of Powder 2 were determined in the same manner as for Powder 1, and were as follows: ·BET specific surface area: 63.5m 2 / g Total pore volume: 0.43cm 3 / g

[0105] 4, it was confirmed that the number of live bacteria decreased most rapidly over time and the antibacterial activity was the highest when Powder 1 was added. Therefore, it was confirmed that the powder of the present invention (Powder 1) containing aluminosilicate granules having pores with a pore size of more than 200 nm (coarse pores) exhibits superior antibacterial activity to the powder (Powder 2) containing aluminosilicate granules without coarse pores.

[0106] [Example 2] In the procedure for obtaining powder 1, first, a mold-containing powder was obtained in the same manner as in the procedure for obtaining powder 1, except that spray drying was performed under the spray drying conditions of a four-fluid nozzle atomization method and a spray air pressure of 0.20 MPa. The obtained mold-containing powder was subjected to a firing treatment in an air atmosphere to remove the mold particles. Specifically, the temperature was raised at 4° C. / min, the firing temperature was set to 900° C., and the firing time was set to 1 hour. The powder obtained by the above steps will be referred to as "powder 3" hereinafter. Powder 3 obtained by the above procedure was treated with acid to obtain powder 3A. The acid treatment was carried out by mixing hydrochloric acid and Powder 3A at a solid-liquid ratio (mass ratio) of 100:3.5 (hydrochloric acid:powder 3) using 6 mol / L hydrochloric acid, and leaving the mixture at room temperature for 18 hours. After the acid treatment, the mixture was washed with ion-exchanged water, separated into solid and liquid, and then dried at 110°C to obtain Powder 3A. When Powder 3 and Powder 3A were analyzed by XRF, the SiO2 / Al2O3 molar ratio was 2.0 in Powder 3, whereas the SiO2 / Al2O3 molar ratio was 7.0 in Powder 3A. In other words, it is considered that Al2O3 was dissolved by the acid treatment.

[0107] The BET specific surface area and total pore volume of Powder 3 were determined in the same manner as for Powder 1, and were as follows: ·BET specific surface area: 60.8m 2 / g Total pore volume: 0.44cm 3 / g The BET specific surface area and total pore volume of Powder 3A were determined in the same manner as for Powder 1, and were as follows: ·BET specific surface area: 352.2m 2 / g Total pore volume: 0.76cm 3 / g For Powder 3 and Powder 3A, the nitrogen adsorption isotherms were measured in the same manner as for Powder 1, and the pore size distribution was analyzed by the BJH method. The results are shown in FIG. In the graph of Fig. 7, two or more pore diameter peaks are confirmed within the range of 10 nm or more (more than 8 nm and less than 200 nm), and in Powder 3A, a pore diameter peak is further observed around 2 nm. Therefore, it was confirmed that the acid treatment generates a third pore with a pore diameter of 8 nm or less.

[0108] Powder 3 and Powder 3A were also observed by SEM. Observation images of Powder 3 are shown in Fig. 8 and Fig. 9. Fig. 9 is an enlarged observation image of Powder 3. Observation images of Powder 3A are shown in Fig. 10 and Fig. 11. Fig. 11 is an enlarged observation image of Powder 3A. 8 to 11, it was confirmed that the coarse pore structure seen in Powder 3 was also maintained in Powder 3A. That is, it was confirmed that Powder 3A was a powder with a novel structure having coarse pores, pores having a pore size of more than 8 nm and not more than 200 nm, and third pores having a pore size of 8 nm or less.

[0109] [Example 3] In the procedure for obtaining the above-mentioned powder 3, calcium carbonate particles (average particle diameter 3.5 μm) were used as template particles, and 20 parts by mass of calcium carbonate particles were added to 80 parts by mass of the solid content of the slurry. Other than the above, spray drying was performed in the same manner as in the procedure for obtaining the powder 3, and a template-containing powder was obtained. The resulting mold-containing powder was subjected to a sintering treatment in an air atmosphere. Specifically, the temperature was raised at 4° C. / min, and the mixture was fired in an air atmosphere at 650° C. for 1 hour to obtain powder 4. Powder 4 (mold-containing powder) obtained by the above-mentioned firing treatment was subjected to an acid treatment to remove the mold particles (calcium carbonate particles), thereby obtaining Powder 4A. The acid treatment was carried out by using hydrochloric acid with a concentration of 6 mol / L, mixing the hydrochloric acid and the mold-containing powder in a solid-liquid ratio (mass ratio) of hydrochloric acid:powder 4 of 100:4, and performing the acid treatment at 60° C. for 2 hours. After the acid treatment, the mixture was washed with ion-exchanged water, separated into solid and liquid, and then dried at 110° C. to obtain powder 4A. Powder 4 and Powder 4A were analyzed by XRF, and CaO was not detected in Powder 4A. In addition, the SiO2 / Al2O3 molar ratio in Powder 4 was 2.0, whereas the SiO2 / Al2O3 molar ratio in Powder 4A was 42.0. In other words, it is considered that CaO was removed from Powder 4 by the acid treatment, and part of the Al2O3 contained in Powder 4 was dissolved. The BET specific surface area and total pore volume of Powder 4 were determined in the same manner as for Powder 1, and were as follows: ·BET specific surface area: 56.5m 2 / g Total pore volume: 0.46cm 3 / g The BET specific surface area and total pore volume of Powder 4A were determined in the same manner as for Powder 1, and were as follows: ·BET specific surface area: 539.5m 2 / g Total pore volume: 0.67cm 3 / g

[0110] Powder 4A was also observed by SEM. The images of Powder 4A are shown in Figures 12 and 13. Figure 13 is an enlarged image of Powder 4A. As shown in FIG. 12, it was confirmed that the aluminosilicate granules contained in Powder 4A had pores (coarse pores) with a pore size of more than 200 nm. 13, Powder 4A was confirmed to contain granules (aluminosilicate granules) formed by the aggregation of halloysite containing halloysite nanotube particles. Analysis by the BJH method confirmed that there were pores (first pores) derived from the tube pores of the halloysite nanotube particles, as well as pores (second pores) larger in diameter than the tube pores, and a pore diameter peak was present around 2 nm. From the above results, it was confirmed that Powder 4A was a powder with a novel structure having coarse pores, pores with a pore size of more than 8 nm and less than 100 nm, and third pores with a pore size of 8 nm or less.

Claims

1. An aluminosilicate granule comprising nanotube particles and having pores with a pore size of more than 200 nm, the pores are formed by removing template particles from an aluminosilicate granule comprising the template particles and halloysite nanotube particles; The aluminosilicate granules, wherein the nanotube particles are particles derived from halloysite nanotubes.

2. The aluminosilicate granule according to claim 1, further having pores having a size of more than 8 nm and not more than 200 nm.

3. The aluminosilicate granule according to claim 2, comprising, as the pores, first pores derived from the nanotube particles and second pores different from the first pores.

4. The aluminosilicate granule according to any one of claims 1 to 3, further having pores with a pore size of 8 nm or less.

5. The aluminosilicate granule according to any one of claims 1 to 3, comprising a first pore derived from the nanotube particle having a pore diameter of more than 8 nm and not more than 200 nm, a second pore different from the first pore, the second pore having a pore diameter of more than 8 nm and not more than 200 nm, and a third pore having a pore diameter of 8 nm or less.

6. A powder comprising the aluminosilicate granules according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Method for preparing magnetic halloysite molecularly imprinted polymer with specific adsorption to 2,4-dichlorophenoxyacetic acid

    CN103613722A

  • Magnetic viscous fluid

    JP2006286890A

  • Method of producing NANO silicon

    JP2023044813A

  • Halloysite powder

    WO2021172547A1

  • Halloysite powder and method for producing halloysite powder

    WO2018079556A1